Benchmarking—Current Availability, Possible New National Alternatives, and Making a Contribution to the Discussion. Issue 166 (January 2016) - Atchison, Eric S.; Hosch, Braden J.
Abstract : This chapter synthesizes the national discussion on other solutions to the Integrated Postsecondary Education Data System (IPEDS), such as a national student record system, and complications. The authors will briefly examine the pros and cons of IPEDS while primarily focusing on national alternatives, as well providing specific examples for institutional researchers to make a contribution to the field.